Pedagogies of taking care : art, pedagogy and the gift of otherness - Atkinson, Dennis (London [England] : Bloomsbury Academic, 2022)
"This book traces the notion of care and civic values in education that are largely devalued today by neoliberal economic concerns. Through a discussion of educators and philosophers including Arendt, Foucault, Guattari, Patocka, Simondon, Stengers and Whitehead Atkinson explores the 'gift of otherness' in relation to an ethico-politics of pedagogic practice and learning, including art education. He argues for pedagogical practices that facilitate and support each learner's pathways through what is called a pedagogy of taking care. This involves paying due attention, with empathy, to each learner's pathway of learning and to the difference and divergence of such pathways. It also requires the teacher to take care, to be vigilant towards their own pedagogical frameworks that inform pedagogical work, particularly when a student or child produces work that does not accord with such frameworks. Atkinson not only critiques the world as it is, but offers possible futures of being, not dominated by the neoliberal tools of force and power. Pedagogies of care allow us to think differently about education and art education, and revaluate it's meaning within research, classrooms, non-formal contexts of education and cultural institutions."--
Introduction: An Ethico-Aesthetic Project for a Pedagogy of Taking Care -- 1. Changing the Value of the Currency in Pedagogic Work -- 2. Pedagogy, Conditions and Value -- 3. Gilbert Simondon's Transduction and Pedagogic Practice -- 4. On the Idea of Speculative Pedagogies -- 5. The Scandal of the Truth of Art and its Implications for Art in Education -- 6. The Gift of Otherness -- 7. Pedagogic Work and Art Practice -- 8. Pedagogy of the Interstices -- Conclusion -- References -- Index.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Education -- Aims and objectives; Art -- Study and teaching; Educational psychology; Other (Philosophy); Philosophy & theory of education; Moral & social purpose of education; Educational: Art & design; Electronic books